A LONG-TERM SURVEY OF JAPANESE LANGUAGE PROFICIENCY OF CLD CHILDREN LIVING IN JAPAN - Fukihara, Yutaka; Sukegawa, Yasuhiko; Najoan, Franky R. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
In Japan, there are several areas where Indonesian migrants live in concentration and in such areas, problems arise about children’s education at schools. A continuous five-year survey on the children of Indonesian migrant workers was conducted to assess their Japanese language proficiency and language skills which are necessary for academic learning, identifying challenges, and implementing improvements. The survey participants were 21 Indonesian children enrolled in the Japanese language class at A Elementary School in an area with a high population of Indonesian migrant workers. These children were born and raised in Japan, and many had lived in Japan for many years having received Japanese language instruction at school. The survey used the Dialogic Language Assessment for Foreign Students (DLA) to measure the children’s abilities. Each year, interviews and tests were conducted to assess their learning progress. Additionally, interviews were conducted with two teachers. There were mainly two findings; (1) Three students who received specialized instruction from elementary school teachers developed reading comprehension and conversational skills comparable to those of native Japanese speakers. (2) Some children showed improvement in their Japanese language proficiency, though they had not yet reached the level of native speakers. Conversely, some children faced serious academic challenges owing to incomplete language proficiency. The survey found out that there was an obvious correlation between reading habits and Japanese proficiency of the children. The study indicated that reading habits apparently contribute to improving language skills.